Self-Reported Seat Discomfort Among Dutch Commercial Truck Drivers - Tan, Chee Fai; Chen, Wei; Rauterberg, Matthias (2010)
Comfort is an attribute that today’s consumers demand more and more. The seat has an important role to play in fulfilling these comfort expectations. Seating comfort is a major concern for drivers and other members of the work force who are exposed to extended periods of sitting and its associated side effects. In this paper, we described of the survey that examine the seat discomfort and travel time factors for Dutch commercial truck driver. For the survey, the self-administered questionnaires were completed by 217 truck drivers in the Netherlands. Statistical methods such as factor analysis and one way ANOVA were used to find the differences between body discomfort of truck drivers after one hour and five hours sitting while driving. The results showed that truck drivers experienced different level of body discomfort for one hour and five hours sitting while driving. Subsequently, the survey also found that there is significant discomfort at different body part. The outcomes from the analytical results were important and required more attention to reduce the body discomfort for long hour sitting.